Effects of sunlight on the abundance of Euglenophyceae in earthen ponds - Mandal, R. B.; Rai, S.; Shrestha, M. K.; Jha, D. K.; Pandit, N. P. (Journal of Agriculture and Forestry University, 2020)
Algal red bloom in carp ponds has been a serious concern to farmers due its scum covering the entire pond surface area during the day and disappearing in the evening. Thus it is important to examine the effects of sunlight on dynamics of red bloom algae in ponds. An experiment was done with the use of three treatments, i) non-red bloom pond with sunlight, ii), red bloom pond with sunlight, and iii) red bloom pond without sunlight; each treatment was replicated thrice. Density of Euglenophyceae was assessed from two different water depths (10 cm and 50 cm) at three different times: morning, afternoon, and evening. Results showed that Euglena sanguinea Ehrenberg, 1832 was dominant among euglenophytes and it showed vertical and temporal migration with sunlight intensity. Density of E. sanguinea was significantly higher (p<0.05) at 10 cm and lower (p<0.05) at 50 cm in the afternoon. Preventing sunlight to the red bloom pond decreased density of Euglenophyceae and E. sanguinea by 69% and 80%, respectively. Maximum red bloom was observed during 12.00 to 13.00 hours, when light intensity was highest (1928 Lux to 1988 Lux). Appearance and disappearance of red bloom in the pond was due to vertical migration of E. sanguinea with sunlight intensity.